Antioxidant Activity of Flaxseed Extracts in Lipid Systems - Adriana Slavova-Kazakova; Magdalena Karamać; Vessela Kancheva; Ryszard Amarowicz (Molecules, 2015)
The aim of this work was to compare the antioxidant activity of the extract of flaxseed and its alkaline hydrolysate in two model systems: lipid autoxidation of triacylglycerols of sunflower oil (TGSO)—in a homogeneous lipid media and during β-carotene-linoleate emulsion system. In addition, pure lignans were tested. The material was defatted with hexane and then phenolic compounds were extracted using dioxane-ethanol (50:50, v/v) mixture. Carbohydrates were removed from the crude extract using an Amberlite XAD-16 column chromatography. The content of total phenolic compounds in the crude extract and after alkaline hydrolysis was determined using a Folin-Ciocalteu’s phenol reagent. Individual phenolic compounds were determined by nordihydroguaiaretic acid (RP-HPLC) method in gradient system. The alkaline hydrolysis increased the content of total phenolics in the extract approximately by 10%. In the extracts of flaxseed, phenolic compounds were present in the form of macromolecular complex. In the alkaline hydrolysate, secoisolariciresinol diglucoside (SDG) was found as the main phenolic compound. Small amounts of p-coumaric and ferulic acids were also determined. SDG and both extracts were not able to inhibit effectively lipid autoxidation. The kinetics of TGSO autoxidation at 80 °C in absence and in presence of the extract before hydrolysis (EBH) and after hydrolysis (EAH) was monitored and compared with known standard antioxidants. Ferulic acid (FA) and butylated hydroxyl toluene (BHT) showed much higher antioxidant efficiency and reactivity than that of both extracts. Secoisolariciresinol (SECO) showed a higher activity in both model systems than SDG. However, the activity of SECO was much lower than that of nordihydroquaiaretic acid (NDGA).